Screening of extraction properties of nanofibers in a sequential injection analysis system using a 3D printed device - Šrámková, Ivana H; Carbonell-Rozas, Laura; Horstkotte, Burkhard; Háková, Martina; Erben, Jakub; Chvojka, Jiří; Švec, František; Solich, Petr; García-Campaña, Ana M; Šatínský, Dalibor (Talanta, 2019)
A novel application of the three-dimensional printing technology for the automation of solid phase extraction procedures in a low-pressure sequential injection analysis system is presented. A 3D printed device was used as a housing for nanofiber membranes in solid phase extraction. The applicability of the device is demonstrated with the extraction of substances of various physical-chemical properties. Pharmaceuticals including non-steroidal anti-inflammatory drugs, antihistaminics, and steroidal structures, as well as emerging pollutants such as bisphenols and pesticide metsulfuron methyl were used as model analytes to study the extraction performance of the nanofibers. Six different nanofiber types comprising polyamide, polyethylene, polyvinylidene fluoride, polycaprolactone combined with polyvinylidene fluoride, and polyacrylonitrile, produced by electrospinning were tested in solid phase extraction. The suitability of specific nanofibers for particular analytes is demonstrated.